Graphitic carbon nitride-based nanoplatforms for biosensors: design strategies and applications. (June 2022) - Gupta, N.; Todi, K.; Narayan, T.; Malhotra, B.D.
Abstract: In recent years, nanostructured graphitic carbon nitride (g-CN) nanostructures have emerged as exciting nanomaterials with multiple advantages, including good photoelectrochemical response, fluorescence, biocompatibility, cost-effectiveness, and scalable synthesis. These tailorable properties are by and large dependent upon the different morphologies of nanostructured g-CN, which are further dependent upon the synthesis method utilized. This flexibility in nanostructure design, abundance of functional amine groups and diverse, cost-effective synthesis methodologies have inspired the use of g-CN nanostructures as biocompatible biosensing platforms with various signal transduction modes, including photoelectrochemical, electrochemiluminescence, fluorescence, colorimetric, and electrochemical. This review aims at highlighting the multidimensional uses of g-CN nanostructures toward the development of different types of biosensors. The synthesis methodologies for different morphologies of g-CN have been summarized along with the discussion on their advantages and limitations. Subsequently, the different properties of g-CN nanostructures have been elucidated ranging from thermal and chemical stability to electronic structure and properties. Further, the recent advancements in the field of g-CN-based biosensors are comprehensively reviewed. Finally, future perspectives of this interesting nanomaterial are discussed with a focus on the challenges faced by the current g-CN-based biosensing devices. Graphical abstract: Image 1 Highlights: Different biosensing modalities based on graphitic carbon nitride are summarized. The synthesis methods and different properties of graphitic carbon nitride (g-CN) are discussed. g-CN nanosheets are the most prominently used materials for biosensor fabrication. g-CN can be used as both a sensing platform and signal probe in biosensors. Control of synthesis and doping of g-CN may improve biosensing efficiency.